2017
DOI: 10.1002/joc.5308
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of temperature trends on the southeast Tibetan Plateau, China

Abstract: Based on the monthly mean temperatures recorded between 1961 and 2012 at 14 meteorological stations on the southeast Tibetan Plateau (STP), the temporal and spatial variations in mean seasonal and annual temperature trends were investigated using the Mann–Kendall test. The temperature time series on the STP are mainly characterized by increasing trends, and the rate of warming on the STP is far higher than that in other areas in China and even in other parts of the world. Statistically significant increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The sequential version of the Mann‐Kendall (SVMK) test was developed from the Mann‐Kendall (MK) test (Kendall, ; Mann, ) by Goossens and Berger (). This method has been widely used to detect the abrupt change of trend in climatic time series, including temperature (Karaca et al, ; Wang, ), precipitation (Esteban‐Parra et al, ), and the dry/wet trend (Faustin Katchele et al, ; Ma, ). Thus, the SVMK method is used to detect the abrupt change of soil moisture trend in this work.…”
Section: Methodsmentioning
confidence: 99%
“…The sequential version of the Mann‐Kendall (SVMK) test was developed from the Mann‐Kendall (MK) test (Kendall, ; Mann, ) by Goossens and Berger (). This method has been widely used to detect the abrupt change of trend in climatic time series, including temperature (Karaca et al, ; Wang, ), precipitation (Esteban‐Parra et al, ), and the dry/wet trend (Faustin Katchele et al, ; Ma, ). Thus, the SVMK method is used to detect the abrupt change of soil moisture trend in this work.…”
Section: Methodsmentioning
confidence: 99%
“…During 2008–2018, annual precipitation at the AWS ranged from 180 to 360 mm, with mean annual precipitation of 269 mm, and annual mean air temperatures ranged from −2.3°C to −1.0°C with a mean annual temperature of −1.6°C. S. J. Wang (2018) found that the mean annual temperature of the southeast TP increased by 0.25°C per decade between 1961 and 2012. With a relatively high rate of warming, glaciers over the southeast TP are expected to retreat quickly (Yang et al., 2008).…”
Section: Study Area and Datamentioning
confidence: 99%
“…S. J. Wang (2018) found that the mean annual temperature of the southeast TP increased by 0.25°C per decade between 1961 and 2012. With a relatively high rate of warming, glaciers over the southeast TP are expected to retreat quickly (Yang et al, 2008).…”
Section: Study Areamentioning
confidence: 99%
“…Easterling et al 1997;Frich et al 2002;Zhai and Pan 2003;Gong, Pan, and Wang 2004;IPCC 2007;Zhang et al 2011;IPCC 2013;Song et al 2014;Shen et al 2017;Cheng and Zhu 2018). Under global warming, Southwest China has suffered from extreme heat events for a long time (Liu et al 2006;You et al 2008a;Li et al 2012a;Ma et al 2013;Peng 2014;Li 2015;Qin et al 2015;Jiang et al 2016;Wang 2018). For example, the extreme high temperature event in Sichuan Province in summer 2006 led to more than half of the local meteorological stations reaching a new high-temperature record, resulting in direct economic losses of 10 billion RMB (Li 2015).…”
Section: Introductionmentioning
confidence: 99%